Adsorption behaviors and mechanisms of simultaneous cadmium and fluoride removal on waste bovine bone from aqueous solution. Issue 1 (February 2023) - Wang, Mengting; Ye, Han; Zheng, Xiongkai; Chen, Siyuan; Xing, Huanhuan; Tao, Xueqin; Dang, Zhi; Lu, Guining
Abstract: Cadmium (Cd 2+ ) and fluoride (F - ) are frequently detected simultaneously in wastewater. Simultaneous removal of Cd 2+ and F - in wastewater is urgent. In this study, bovine bone meal (BBM), mainly consisted of hydroxyapatite, was used as a green adsorbent for Cd 2+ and F - adsorption in single and binary solutions. The results showed that with the increase of pH, the uptake ability of BBM towards Cd 2+ and F - showed an upward and downward trend, respectively, suggesting that electrostatic interaction was an important mechanism. Cl - and NO3 - had little effect on Cd 2+ and F - adsorption, while H2 PO4 - enhanced adsorption capacities. The kinetic data of Cd 2+ and F - removal were successfully described by pseudo-second order model. The maximum adsorption capacity (qm ) of Cd 2+ obtained from the Langmuir model was 78.969 mg/g. The adsorption isotherm of F - was consistent with S-type and satisfied with the Brunauer, Emmett, and Teller (BET) model. In the binary system, F - slightly decreased the adsorption capacity of BBM on Cd 2+, while Cd 2+ increased the adsorption capacity of BBM on high-concentration F - from 38.724 to 86.966 mg/g. This study provides a cost-effective and environmentally friendly method for separate and simultaneous removals of Cd 2+ and F - from water, which provides a practicable way for the treatment of cadmium-fluorine wastewater and resource utilization of bovine bone. Highlights: F - slightly inhibited Cd 2+ adsorption on bovine bone meal. Cd 2+ significantly promoted F - adsorption capacity. Complexation, ion exchange and electrostatic attraction were contributed to binary adsorption. BBM effectively removed Cd 2+ and F - individually and simultaneously from solution.